Transformative violence: when routine cruelty sparks historic mobilization - Marat, Erica (Oxford University Press, 2024)
"Why are some violent acts more galvanizing than others? By examining mobilization following the gang rape of a 23-year-old student in New Delhi in 2012 and the disappearance of 43 students in Mexico in 2014, the book builds a theoretical explanation of how some violent acts can trigger unprecedented levels of mobilization in defense of the victims. While such events - transformative violence - emerge from complex networks of causal mechanisms, they all draw sharp moral contrasts between the typical victims and repressors in a society. Cases of violence that spark large public reaction share similar set of traits - they include mobilization of both grassroots and national-level activists, a type of victim that resonates with the broader public, and a visual narrative of the victim's suffering"--